Kenaikan Utang Luar Negeri Dalam Sistem Ekonomi Makro Modern - Nuraini, Airin; Roup, Abdul (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
The macroeconomic conditions in Indonesia and other third world countries have never been separated from economic problems, one of which is high foreign debt. This is indicated because of the vicious cycle that occurs in the modern macroeconomic system (Nuraini, 2020), namely if the monetary sector is larger than the real sector or an increase in the money supply occurs, inflation or economic bubbles will occur, the way to overcome this is with a contraction policy to reduce the amount. money supply, and later the economy will slow down, if the economy slows down, it will be overcome by expansion policies to increase the money supply, one of which is a fiscal deficit policy, a fiscal deficit policy means that expenditure is greater than income, the difference will be financed the largest by debt so that debt will always be experiencing an increase, the form of foreign debt which refers to the dollar exchange rate will ultimately make the amount of debt and interest bigger and continue to increase and so turn in the circle. The purpose of this study is to empirically determine the effect of the fiscal deficit policy, the money supply, the foreign debt of the previous period, and the exchange rate (USD exchange rate) on the increase in External Debt (ULN), especially in Indonesia in the vulnerable period of 1989 to 2018. The result is that all independent variables have a significant and significant effect on foreign debt with a Goodness of fit of 97.57%